Role of Macrophage in Tumor Microenvironment: Prospect in Cancer Immunotherapy. (January 2013) - Gautam, P.K.; Deepak, P.; Kumar, S.; Acharya, A.
Current evidence suggests an increasing role of macrophages in inflammation and tumor progression. Most tumors contain an abundant number of macrophages as a major component of their leukocyte infiltrate, which co-exist with tumor cells at the tumor microenvironment. Upon activation with soluble tumor antigens, macrophages release a distinct repertoire of growth factor, cytokines, chemokines and enzymes that inhibit growth of the tumor. However, the anti-tumor immune response induced by macrophages does not always ensue. Tumor cells themselves are capable of down-regulating macrophage phenotype and functions and anti-tumor immune responses in the tumor-bearing host. The present review aims to elucidate the role of macrophages in tumor growth and progression, invasion, metastasis, and angiogenesis at the site of tumor growth. Moreover, the effect of tumor microenvironment on the phenotype and function of macrophages, which are altered due to the continuous exposure of various soluble and non-soluble tumor promoting factors secreted by tumor cells, and implication of macrophages in cancer immunotherapy have been discussed in detail.